The Maritime Silk Road Global Connectivities, Regional Nodes, Localities - Billé, Franck; Mehendale, Sanjyot; Lankton, James (Asian Borderlands, 2022)
The Maritime Silk Road foregrounds the numerous networks that have been woven across oceanic geographies, tying world regions together often far more extensively than land-based routes. On the strength of the new data which has emerged in the last two decades in the form of archaeological findings, as well as new techniques such as GIS modeling, the authors collectively demonstrate the existence of a very early global maritime trade. From architecture to cuisine, and language to clothing, evidence points to early connections both within Asia and between Asia and other continents-well before European explorations of the Global South. The human stories presented here offer insights into both the extent and limits of this global exchange, showing how goods and people traveled vast distances, how they were embedded in regional networks, and how local cultures were shaped as a result.